2019
DOI: 10.1002/kjm2.12155
|View full text |Cite
|
Sign up to set email alerts
|

miR‐922 regulates apoptosis, migration, and invasion by targeting SOCS1 in gastric cancer

Abstract: Gastric cancer (GC) is the second leading cause of cancer‐related death worldwide. Studies have shown that miR‐922 facilitates the development of various diseases and tumors. However, the role of miR‐922 in GC and related molecular mechanisms are still unrevealed. Current study indicated that miR‐922 was overexpressed in GC tissues and cells. The survival rate of patients in high miR‐922 expression group is significantly lower than that in low miR‐922 expression group. In addition, overexpression of miR‐922 ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Secondly, it may be involved in ubiquitination and subsequent proteasomal degradation as a substrate-recognition module via the recruitment of E3 ubiquitin ligases complex [36,37]. Previous studies demonstrated that SOCS1 was low expression in many types of cancer, such as anaplastic thyroid cancer [38], gastric cancer [39], hypopharyngeal carcinoma [40], and breast cancer [41]. however, several studies have also shown that SOCS1 expression level was increased in colorectal cancer [42], glioblastoma [43], and triple-negative breast cancer [44].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it may be involved in ubiquitination and subsequent proteasomal degradation as a substrate-recognition module via the recruitment of E3 ubiquitin ligases complex [36,37]. Previous studies demonstrated that SOCS1 was low expression in many types of cancer, such as anaplastic thyroid cancer [38], gastric cancer [39], hypopharyngeal carcinoma [40], and breast cancer [41]. however, several studies have also shown that SOCS1 expression level was increased in colorectal cancer [42], glioblastoma [43], and triple-negative breast cancer [44].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs control expression of their target mRNAs principally by binding to the 3'-untranslated region (3'-UTR) to inhibit the translation of mRNA and decrease its half-life. miR-922 is a tumor-promoting gene that promotes the development and progression of tumors (6,7). miR-922 expression levels are decreased in breast cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…miR-922, which has been found to be overexpressed in GC, targets the SOCS1 gene and negatively regulates its expression by activating the JAK and AKT pathways, promoting tumor cell proliferation and motility. Conversely, downregulation of miR-922 increases SOCS1 expression and promotes the apoptosis of GC cells ( 52 ).…”
Section: Epigenetic Modulations Of Cytokines In Gcmentioning
confidence: 99%